Implementation Improvement Analysis of M-Library Application and Related Business Processes at XYZ University - Rizqiyatul Khoiriyah; Devi Handayani; Tungga Bhimadi (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
XYZ University library provides offline and online book loan services. The library's online service uses the m-library application. This study aims to see the implementation of the m-library application and see the extent of the evaluation of the application. The m-library application is used for the process of borrowing books, viewing catalogs, and reading book online. The method used in this research is qualitative descriptive through interviewing interviewees and observing applications. The results of this study are that there are several benefits and weaknesses to the m-library application. From these shortcomings, it can be recommended to increase the implementation of the m-library application, namely the need for application development towards menu flexibility and application services, ease of online membership registration process, compatibility of online and offline book catalogs and more effective use of application features according to the University library business process. This application also requires broader socialization to the university academic community so that its use is more optimum.